Marketing Strategy Innovation: Enhancing Competitiveness and Differentiation of Local Products in the Global Market - Desman Serius Nazara (Oikonomia : Journal of Management Economics and Accounting, 2025)
Innovation in marketing strategy is an important element in improving the competitiveness and differentiation of local products in the midst of increasingly fierce global market competition. Local products, despite their high cultural value and uniqueness, often face challenges in expanding their market reach and competing with products from international brands. This research aims to analyze how marketing strategy innovation can be effectively used to increase the competitive value of local products and differentiate them from other products in the global market. Through a qualitative approach with literature study and case study analysis, this research identifies several key elements in innovative strategies, such as the use of digital technology (including social media and e-commerce), the development of a strong brand image based on local wisdom, product personalization according to the needs of the international market, and communication strategies that are adaptive to the culture of the target market. The findings show that when local businesses are able to adopt innovative marketing approaches that are responsive to global market dynamics, they can not only increase product visibility, but also build international consumer loyalty. In addition, collaboration with stakeholders such as the government, creative communities, and global distribution platforms also strengthens the position of local products. This research is expected to serve as a reference for MSMEs, local brand developers, and policy makers in formulating marketing strategies that are relevant, sustainable, and able to elevate local potential to the global level